The brain effects of laser acupuncture at thirteen ghost acupoints in healthy individuals: A resting-state functional MRI investigation. (December 2016) - Lv, Jian; Shi, Changzheng; Deng, Yanjia; Lou, Wutao; Hu, Jing; Shi, Lin; Luo, Liangping; Wang, Defeng
Highlights: The changes in brain's ReHo/ALFF were demonstrated after laser acupuncture by using rs-fMRI. The brain regions with increased/decreased ReHo or ALFF value play important roles in cognitive function. The laser acupuncture at thirteen ghost acupoints may help for cognition modulating. Abstract: Acupuncture at thirteen ghost acupoints (TGA) was an effective treatment of neuropsychological disorders. However, the underlying neurological mechanisms of acupuncture at the TGA have not been revealed by modern scientific technologies. As laser acupuncture emerges with the painless and noninvasive advantages and the functional magnetic resonance imaging (fMRI) allows us to investigate the activation of the brain in vivo, we performed the preliminary study to investigate the relation to brain effects of acupuncture at TGA based on resting-state fMRI (rs-fMRI). Twenty one healthy subjects underwent rs-fMRI scan before and after acupuncturing TGA (except HI11 and CV1). The regional homogeneity (ReHo) values and the amplitude of low-frequency fluctuation (ALFF) values were evaluated within the whole brain and compared before and after laser stimulation of TGA. We found increased ReHo/ALFF value in serious brain regions, including right inferior occipital gyrus, bilateral middle occipital gyrus, left inferior temporal gyrus, and bilateral postcentral gyrus, after acupuncture. While, significantly decreased ReHo/ALFF value was found in the cerebellum, left superior medial frontal gyrus, left precuneus, right middle temporal gyrus, right middle frontal gyrus and left superior parietal lobule after laser stimulation. The changes in brain spontaneous function after laser acupuncture may suggest that acupuncturing at TGA may have the potential modulating effect of the cognitive functions. These preliminary findings of the changes of brain patterns at resting-state after TGA stimulation may lay the groundwork for further studies on its therapeutic effect in some neuropsychological disease models.